"United in diversity": The interplay of social network characteristics and personality in predicting outgroup attitudes. (August 2022) - Bobowik, Magdalena; Benet-Martínez, Verónica; Repke, Lydia
Diversity in social relations is important for reducing prejudice. Yet, the question of when this occurs remains open. Using a social network approach, we test whether the link between outgroup attitudes and number of intra- and intergroup contacts is moderated by type of relationship (strong vs. weak ties) and personality (openness to experience) while also considering network structure (connections between contacts). In a culturally diverse sample of 122 immigrants residing in Barcelona, positive outgroup attitudes were predicted by several network characteristics: low proportion of intragroup contacts and high proportion of intergroup contacts among strong ties, high ethnic diversity among strong ties, low connectedness among contacts in the country of origin, and high connectedness between coethnic local and host national contacts. Openness to experience moderated these effects. These results affirm the intergroup benefits of having compositionally and structurally diverse networks, and the gain in examining intergroup dynamics at the meso level of analysis.